1999
DOI: 10.2118/99-13-11
|View full text |Cite
|
Sign up to set email alerts
|

Barite Segregation In Inclined Boreholes

Abstract: Settling and sagging of barite in inclined boreholes may lead to safety and operational problems. To study the effect of rheology on settling, a laboratory tool was designed, consisting of two connected tubes, one inclined and one vertical. The hydrostatic pressure was measured at the bottom of each pipe. Stable and unstable muds can clearly be differentiated through their pressure behaviour. Several muds were studied at simulated static and dynamic conditions. The results show that sagging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
(12 reference statements)
2
11
0
Order By: Relevance
“…At 0.5 lb/bbl of laponite, the vertical and inclined sag factor decreased from 0.569 and 0.58 to 0.532 and 0.542, respectively, and these values are still above the acceptable value, while adding 0.75 lb/bbl brought the sag factor to the safe range with a sag factor of 0.502 and 0.51; therefore, less sag tendency is anticipated at that conditions. It was observed that the drilling fluid always performed better in vertical conditions than in inclined conditions because the inclination angle contributes significantly to the sagging phenomenon, and the critical range of inclination is between 30 and 60° as reported in previous studies. , Similarly, the base fluid, without laponite, showed unfavorable sag tendency at dynamic conditions with a sag factor (VSST) of 2.3 (Figure . Adding 0.5 lb/bbl of laponite significantly improved the mud homogeneity and reduced the VSST to 1.54, which is still above the acceptable value (below 1). , Increasing the concentration of laponite to 0.75 lb/bbl substantially reduced the VSST to 0.17.…”
Section: Results and Discussionsupporting
confidence: 70%
“…At 0.5 lb/bbl of laponite, the vertical and inclined sag factor decreased from 0.569 and 0.58 to 0.532 and 0.542, respectively, and these values are still above the acceptable value, while adding 0.75 lb/bbl brought the sag factor to the safe range with a sag factor of 0.502 and 0.51; therefore, less sag tendency is anticipated at that conditions. It was observed that the drilling fluid always performed better in vertical conditions than in inclined conditions because the inclination angle contributes significantly to the sagging phenomenon, and the critical range of inclination is between 30 and 60° as reported in previous studies. , Similarly, the base fluid, without laponite, showed unfavorable sag tendency at dynamic conditions with a sag factor (VSST) of 2.3 (Figure . Adding 0.5 lb/bbl of laponite significantly improved the mud homogeneity and reduced the VSST to 1.54, which is still above the acceptable value (below 1). , Increasing the concentration of laponite to 0.75 lb/bbl substantially reduced the VSST to 0.17.…”
Section: Results and Discussionsupporting
confidence: 70%
“…Higher concentration (>40 wt.%) is not required, and it will increase the cost of the drilling fluid. The static sag factor at an inclination of 45 • was slightly higher than at vertical conditions because solids settlement is accelerated at inclination between 30 • and 60 • [20,42]. The optimum ilmenite concentration, however, may vary with the used drilling fluid formulations and well conditions which require optimizing the ratio of ilmenite to barite for each formulation before field applications.…”
Section: Resultsmentioning
confidence: 99%
“…A static sag test was performed to study the effect of ilmenite on sag tendency of barite-weighted drilling fluid in static conditions. The test was conducted in vertical and inclined conditions (45°) because the solids sag issue becomes more serious at an inclination angle above 30° [33]. Figure 3 shows the experimental set-up used to perform the static sag test.…”
Section: Methodsmentioning
confidence: 99%